A dialogue on the erosion, subversion, and reclamation of academic freedom - Mahabeer, P.; Amin, N. (South African Journal of Higher Education, 2025)
This study examines the complex landscape of academic freedom in South African higher education and explores its historical context, challenges and perspectives. Using a dialogue-based approach, we examine the mechanisms of erosion and control that threaten academic freedom, as well as the strategies to subvert and reclaim it. A triad of theoretical lenses is employed to interpret the dialogue, drawing on the works of Foucault, Marcuse and Crenshaw. The article emphasises the paradoxical nature of academic freedom, drawing on Jacques Derrida’s concept of the pharmakon. We argue for a contextual approach to academic freedom that recognises both its crucial importance for social progress and its potential for abuse. The paper concludes with a call for continued critical reflection, institutional reform and a commitment to promoting diverse and inclusive academic communities as important steps towards redefining academic freedom in the South African context.